Finding Sanctuary and Strength in the LIS Classroom - Hartel, Jenna; Latham, Kiersten; Tench, Beck; Samson, Hugh; Siracky, Hailey; Chabot, Roger (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
In the spirit of contemplative pedagogy, this panel introduces The Tree of Contemplative Practices – a graphic representation that helps educators and students to understand the main principles and seven major types of contemplative practices. Using the Tree as a framework, enthusiasts can learn contemplative practices in a systematic, secular, and bespoke manner. Sequentially, the moderator and presenters will: 1) Encapsulate their commitment to contemplative pedagogy; 2) Recount an application of The Tree of Contemplative Practices in their teaching; and 3) Demonstrate several of the Tree’s major limbs (e.g. generative) and branches (e.g. loving-kindness meditation).